2021
DOI: 10.3390/ma14010194
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Characteristics and Constitutive Equations for the Semi-Solid Isothermal Compression of Cold Radial Forged 6063 Aluminium Alloy

Abstract: Al-Mg-Si based alloys are popular alloys used in the automotive industry. However, limited studies have been performed to investigate the microstructure, deformation characteristics, and deformation mechanism for the semi-solid 6063 alloys. In this study, the cold radial forging method and semi-solid isothermal treatment (SSIT) are proposed in the semi-solid isothermal compression (SSIC) process to fabricate high-quality semi-solid 6063 billets. The effects of deformation temperature, strain rate, and strain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…As shown in Figure 6a, the RF-deformed 7075 aluminum alloy blank had four different diameters, indicating the FRs of 30.56%, 42.91%, 52.54%, and 75%, respectively. The value of the FR increases with the decrease in the diameter, which represents an elevation in the strain energy stored in the RF-deformed blank, when the diameter decreases under the RFPD process [52]. As presented in Figure 6b-e, the RF-deformed blanks with different FRs had smooth surfaces without any defects, such as surface cracks or pits, which indicated that the 7075 aluminum alloy with a diameter of 90 mm used in this work can be successfully deformed by the RFPD process, with an FR up to 75%.…”
Section: Effect Of Fr On the 7075 Aluminum Alloy Blankmentioning
confidence: 99%
“…As shown in Figure 6a, the RF-deformed 7075 aluminum alloy blank had four different diameters, indicating the FRs of 30.56%, 42.91%, 52.54%, and 75%, respectively. The value of the FR increases with the decrease in the diameter, which represents an elevation in the strain energy stored in the RF-deformed blank, when the diameter decreases under the RFPD process [52]. As presented in Figure 6b-e, the RF-deformed blanks with different FRs had smooth surfaces without any defects, such as surface cracks or pits, which indicated that the 7075 aluminum alloy with a diameter of 90 mm used in this work can be successfully deformed by the RFPD process, with an FR up to 75%.…”
Section: Effect Of Fr On the 7075 Aluminum Alloy Blankmentioning
confidence: 99%
“…Optimum deformation conditions for both states are temperatures from 500 °C to 520 °C, and strain rates ranging from 0.01 s −1 to 0.1 s −1 for the as-cast material as well as a strain rate of 1 s −1 for the TRC material. Wang et al [ 5 ] proposed the cold radial forging method and semi-solid isothermal treatment in the semi-solid isothermal compression (SSIC) process to fabricate high-quality, semi-solid billets of 6063 aluminum alloy. Constitutive equations were established based on the experimental data to predict the flow stress.…”
mentioning
confidence: 99%